Multiscale approach to characterize effective mechanical, hydraulic and acoustic properties of a new bio-based porous material. (March 2021) - Nguyen, Q.-B.; Nguyen, V.-H.; Perrot, C.; de Anda, A. Rios; Renard, E.; Naili, S.
Abstract: This paper is a multi-aspect study which has undertaken essential numerical characterizations of not only mechanical and hydraulic properties but also acoustic behaviour of a new bio-based porous epoxy resin obtained by a 'green' adapted combination of the cationic photopolymerization and the porogen leaching technique. This new kind of material generally possesses interconnected fillet-edge cubic pores which lead to more complex morphology than in the case of spherical or cylindrical pores. In order to characterize the effective properties of the material, a multiscale approach using the asymptotic homogenization method has been applied. Such a method has induced cell problems whose resolutions have been conducted on the geometrical configuration defined from the experimental data of the samples by using scanning electron microscopy (SEM) and mercury intrusion porosimetry (MIP). The sound absorption behaviour of a plate made of the studied material has been subsequently characterized by solving a normal incidence acoustic problem with an assumption of rigid impervious backing. The mechanical model has been validated by balancing numerical results of the sound absorption coefficient, reflection coefficient, surface impedance, equivalent dynamic density and equivalent dynamic bulk modulus with corresponding experimental results obtained by conducting the three-microphone impedance tube testing. As a consequence, the mechanical model has been applied to investigate the influence of microstructural characteristics on effective properties and acoustic performance of the material. To the authors' knowledge, the features of the microstructure obtained from an elaboration process using the porogen leaching technique have rarely been studied in the literature. Four types of ordered pore arrangements together with systematic variations of the porosity and the pore size have been taken under consideration. Based on the results of these investigations, the subtle relation between microstructures and properties has been established. The processing parameters of material elaboration could be adjusted so that the obtained porous material would possess the best sound absorption performance.